Nanometric Micelles with Photo‐Triggered Cytotoxicity. (24th June 2014) - Anilkumar, Parambath; Gravel, Edmond; Theodorou, Ioanna; Gombert, Karine; Thézé, Benoit; Ducongé, Frédéric; Doris, Eric
<x xml:space="preserve">Abstract</x> The development of a photo‐responsive micellar system capable of triggering cell death is reported. Precursors of the micelles are synthesized by connecting a lipophilic chain to a hydrophilic polyethylene glycol via a photo‐labile nitrobenzyl group. The resulting amphiphilic units are self‐assembled in water forming 12 nm micelles that are readily internalized into cells. Upon photo‐irradiation, micelles undergo cleavage and yield a cytotoxic nitrosobenzaldehyde derivative, which significantly inhibits the proliferation of MDA‐MB‐231 cells under standard in vitro conditions.